Downstream evolution of wastewater treatment plant nutrient signals using high‐temporal monitoring. Issue 3 (2nd December 2019) - Ledford, Sarah H.; Toran, Laura
Abstract: Wastewater treatment plants are major point‐sources of nutrients to streams globally, but the impact on receiving streams is not always clear. Previous research has shown mixed responses in receiving streams, with some showing no net retention through in‐stream processing for large distances below plants and some showing high rates of processing and retention. This study focuses on Sandy Run, a small, suburban stream in Montgomery County, PA, that receives effluent from two plants, where effluent makes up an estimated 50% of outlet discharge at baseflow. Two sites were monitored in late summer baseflow using high‐temporal loggers to evaluate nitrate and phosphate retention with distance below the plants. Effluent quantity was monitored immediately below the effluent outfalls using specific conductivity as a conservative signal of solute fluctuations throughout the day. A site 1 km downstream showed diel nitrate changes, but despite moderate gross primary productivity and ecosystem respiration rates, there was little net retention of nutrients and the diel nitrate signal can be attributed to advection and dispersion of variable upstream effluent. A site 5.4 km below the plant showed a diel nitrate signal as well, but baseflow daily hysteresis plots of nitrate and specific conductivity showed the effluent and nitrate peaks did not coincide. Instead, the effluent input signal was seen overnight, but there was in‐stream removal and release processes during the day. Over the distance to this site, the stream was metabolizing some of the high nutrient loads, although gross primary productivity and ecosystem respiration rates were lower. It is important to understand subdaily changes in nutrient processing to fully quantify the impacts of effluent on small streams at different scales. Furthermore, looking at the diel signal without considering conservative transport would overestimate in‐stream processing. Abstract :